Transmissão vertical e localização do Papaya Meleira Virus (pmev) em tecidos embrionários de Carica Papaya L. - Oliveira, Scarlett dos Anjos (2019)
Papaya (Carica papaya L.) is a fruit of great economic importance for Brazil and for the Espírito Santo state. However, great economic losses have been attributed to papaya sticky disease (PSD) which affects the fruit production in Brazilian and Mexican orchards. The disease is attributed to a combined infection of papaya meleira virus (PMeV) and papaya meleira virus 2 (PMeV2), or PMeV complex. In asymptomatic plants it is possible to detect PMeV, but only plants with double infection present typical symptoms of the disease. It has been postulated that PMeV may be a virus of persistent lifestyle in papaya, since it does not induce visible symptoms in simple infection, does not synthesize a movement protein (MP) and has the capacity to infect cells with meristematic potential in somatic embryos. However, transmission through seeds, a common persistent virus dispersion mechanism, has not been described for PMeV. Due to the importance of the seeds for the initiation of the orchards we investigated the PMeV vertical transmission and its distribution in the papaya seed tissues. Asymptomatic fruits from THB variety papaya plants, were collected to obtain the seeds used in this study. Fifty seeds were grown in a germination chamber to obtain seedlings with 45 days-old. These were used to study the PMeV vertical transmission through RT-PCR method followed by gel electrophoresis. We also investigated, through in situ hybridization, the PMeV dsRNA distribution in dormant seed tissues and 15-day-old germinated seedlings. Our results confirm that PMeV can be transmitted to the next generation through infected seeds, since 84% seedlings amplified the approximately 500 bp PMeV fragment. In situ hybridization results have shown that PMeV can infect different seed tissues. In dormant seeds, PMeV was able to infect cells of the spongy parenchyma, cotyledon leaf, endosperm, cortical parenchyma and embryonic axis procambium. In 15-day-old germinated seedlings, the virus was detected in spongy parenchyma cells close to and within the vascular bundles of the cotyledon leaf. No fluorescence signal was detected in the seed coat of both dormant or 15-day-old germinated seedlings. The different distribution of dsRNA in seed tissues at two different seed developmental stages points to possible infection, survival and movement strategies which are discussed in this work.